A STUDY ON INDIAN ECONOMY DURING LOCKDOWN FOR COVID19 PANDEMIC - Tanmoy Samanta (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The COVID-19 epidemic has contributed to a halt to social and economic life. The present study aims to examine the effect on the sectors affected, such as air travel, retail, tourism, capital markets and MSMEs. Foreign and domestic mobility is limited, and GDP growth is substantially reduced by the revenues produced by travel and tourism that contribute 9.2% of the GDP. Profits from aviation declines by 1,56 trillion dollars. In March, Oil plunged to a low of $22 per barrel of 18 years, while FDIPs withdrew huge sums from India of approximately USD 571.4 million. If the current account deficit shrinks, lower oil prices spread through reverse capital flows. Rupee depreciates regularly. A big cash crunch for MSMEs takes place. The crisis has seen such a floating migrant community on foot during a horrible mass exodus. Most of their problems were job loss, daily ration and lack of a social security network. The real GDP growth is -10.28% in 2020 after lockdown due to COVID19. India must reconsider and make it more inclusive about its growth model. COVID 19 also offered India some unique opportunities. In global supply chains, there is an opportunity to become involved, and multinationals in China lose faith. Some reforms are required to Make India' - one of them being labour reforms.